Implementasi Supervisi Klinis Oleh Kepala Sekolah Untuk Meningkatkan Kinerja Guru - Muhammad Sulfahri; Sitti Habibah; Andi Nurochmah (EDUSTUDENT: Jurnal Ilmiah Pendidikan dan Pembelajaran, 2023)
The purpose of this study is to determine the implementation of clinical supervision by the principal to improve teacher performance and find out the driving and inhibiting factors. The approach to this research is the qualitative description. Data analysis techniques use data reduction, data exposure, and conclusions. The results showed that (1) Clinical supervision planning is to compile a program design at the beginning of each semester through limited meetings with the supervision team, compile clinical supervision instruments, and carry out clinical supervision socialization. (2) The implementation of clinical supervision, namely pre-observation, conducts meetings with teachers to be given time to prepare. Observation by checking learning tools and the principal conducting direct observations when the teacher conducts learning in the classroom. Post-observation, including data analysis of observation results through detection of weaknesses and then a return meeting, is held between the supervision team and teachers. (3) clinical supervision evaluation is carried out at the end of the semester by involving all teachers to analyze the success of the clinical supervision program and then recap and use it as a report. Clinical supervision provides advice, direction, and guidance to teachers through in-house training activities and personal and teacher meetings. The driving factor is the teacher's awareness of clinical supervision so that the teacher can verify his own mistakes, while the inhibiting factor is the teacher the form of awkwardness. There is a sense of tension that will be supervised.